A novel approach to enhance the superconducting properties of La1.85Sr0.15CuO4 by inserting Mott insulator Sr2IrO4. (December 2021) - Pandey, Himanshu; Kumar, Manoj; Tripathi, D.; Pandey, S.
Abstract: We study superconducting properties in multilayer thin films consisting of superconducting La1.85 Sr0.15 CuO4 (LSCO) and Mott insulator Sr2 IrO4 (SIO) and report enhanced superconductivity in the optimized samples. These multilayer heterostructures show an increase in superconducting transition temperature ( T C ) as compared to the single-layer LSCO films. The temperature dependence of the SIO single layer is also investigated under thermal activation, Arrhenius-type behaviour, and variable-range hopping mechanisms for different temperature regimes. The decrease in T C beyond an optimum thickness of LSCO in these multilayers is analyzed in the framework of a model based on the assumption of induced superconductivity in the SIO-LSCO interface due to the doping of La and/or oxygen deficiencies into the SIO layers. Graphical Abstract: We study superconducting properties in multilayer thin films consisting of superconducting La1.85 Sr0.15 CuO4 (LSCO) and the Mott insulator Sr2 IrO4 (SIO) and report enhanced superconductivity in optimized sample. These multilayer heterostructures show an increase in superconducting transition temperature (T C ) as compared to the single layer LSCO films. The temperature dependence of SIO single layer is also investigated under thermal activation, Arrhenius-type behaviour, and variable-range hopping mechanisms for different temperature regimes. The decrease in T C beyond an optimum thickness of LSCO in these multilayers is analyzed in the framework of a model based on the assumption of induced superconductivity in SIO-LSCO interface due to the doping of La and/or oxygen deficiencies into SIO layers. ga1 Highlights: Successful growth of multilayered heterostructure consisting of La1.85 Sr0.15 CuO4 (LSCO) and Mott insulator Sr2 IrO4 (SIO). Perfect growth of multilayer structure can be verified by observing good resolved lowangle Kiessig fringes the X-ray reflectivity data. A significant increase in superconducting transition temperature ( T C ) of 25% is achieved with respect to lowest LSCO thickness sample and around 10% over the T C of bulk-like 100 nm thick LSCO film. A maximum in T C is observed for an optimum thickness of LSCO layer of 30 nm in multilayered samples, beyond which T C starts to decrease with further increasing LSCO layer thickness. We have considered the possibility of intermixing of layers near the LSCO and SIO interface or doping/migration of La atoms into the SIO layer. The optimized insertion of the Mott insulator SIO to LSCO layer remarkably enhances T C and hence, opens a direction to achieve superconducting nature in SIO as predicted by various theoretical calculations.